Gastrodin attenuates diabetic cardiomyopathy characterized by myocardial fibrosis by inhibiting the KLK8-PAR1 signaling axis - MingShan Zhang; YuFei Zhang; JingGang He; XinRui Wang; YinYin Wang; LinYan Li; Ling Tao; Min Zhang; Xiangchun Shen (Chinese Medicine, 2024)
Abstract Background Diabetic cardiomyopathy (DCM), characterized by myocardial fibrosis, is a major cause of mortality and morbidity in diabetic patients; the inhibition of cardiac fibrosis is a fundamental strategy for treating DCM. Gastrodin (GAS), a compound extracted from Gastrodia elata protects against DCM, but the molecular mechanism underlying its antifibrotic effect has not been elucidated. Methods In vivo, the effects of GAS were investigated using C57BL/6 mice with DCM, which was induced by administering a high-sugar, high-fat (HSF) diet and streptozotocin (STZ). We assessed the cardiac function in these mice and detected histopathological changes in their hearts and the degree of cardiac fibrosis. In vitro, neonatal rat cardiac fibroblasts (CFs) were transformed into myofibroblasts by exposing them to high glucose combined with high palmitic acid (HG-PA), and CFs were induced by pEX-1 (pGCMV/MCS/EGFP/Neo) plasmid-mediated overexpression of KLK8, which contains the rat KLK8 gene. The KLK8 siRNA was knocked down to study the effects of GAS on CF differentiation, collagen synthesis, and cell migration by specific mechanisms of action of GAS. Results GAS attenuated pathological changes in the hearts of DCM mice, rescued impaired cardiac function, and attenuated cardiac fibrosis. Additionally, the results of molecular docking analysis showed that GAS binds to kinin-releasing enzyme-related peptidase 8 (KLK8) to inhibit the increase in protease-activated receptor-1 (PAR-1), thus attenuating myocardial fibrosis. Specifically, GAS attenuated the transformation of neonatal rat CFs to myofibroblasts exposed to HG-PA. Overexpressing KLK8 promoted CF differentiation, collagen synthesis, and cell migration, and KLK8 siRNA attenuated HG-PA-induced CF differentiation, collagen synthesis, and cell migration. Further studies revealed that a PAR-1 antagonist, but not a PAR-2 antagonist, could attenuate CF differentiation, collagen synthesis, and cell migration. Additionally, GAS inhibited KLK8 upregulation and PAR1 activation, thus blocking the differentiation, collagen synthesis, and cell migration of HG-PA-exposed CFs and triggering TGF-β1/Smad3 signaling. Conclusion GAS alleviated pathological changes in the hearts of DCM model mice induced by an HSF diet combined with STZ. KLK8 mediated HG-PA-induced differentiation, collagen synthesis, and the migration of CFs. GAS attenuated the differentiation, collagen synthesis, and migration of CFs by inhibiting the KLK8-PAR1 signaling axis, a process in which TGF-β1 and Smad3 are involved. Graphical Abstract